Determining what rehabilitation information people obtained during major lower extremity amputation (rehabilitation) in the Nelson Mandela Bay Health District setting - Erasmus, Annemie (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScPhysio)--Stellenbosch University, 2022.